British Sales 1780-1800 : The rise of the London Art Market - The National Gallery; Getty Research Institute (2013)
[Dt.:] Die National Gallerx und das Getty Research Institute haben in Zusammenarbeit britische Auktionskataloge der Jahre 1780-1800 erschlossen. Die Daten sind über den Getty Provenance Index suchbar. - [Engl.:] A collaboration between the National Gallery and the Getty Research Institute to augment records about British art sales in the crucial decades from 1780 to 1800